The fundamentals of coaching and playing baseball - Landolphi, Don.; Russo, Joe, 1944- (Boston : Allyn and Bacon, 1998)
This book is about: Standard system offensive play; The Aggressive approach to hitting; Barerunning: Pressure the defense; Fundamental foundations for pitching; ...
Keywords: Coaching; Baseball; Baseball -- Coaching; Baseball